Automatic drain rubbish collector / Muhammad Farhan Azlan and Azizul Hakim Samsudin - Azlan, Muhammad Farhan; Samsudin, Azizul Hakim (School of Mechanical Engineering, 2023)
Drain system is one of the important systems for excessive water to flow from one point to another. Poor drainage system could lead to the reason flash flood happen to certain area. Poor drainage system might cause by the waste thrown or waste flow into the drain system that make the drain clogged. Morphological approach was used to determine the proper design of the automatic drain rubbish collector. Meanwhile, torque theory was used to determine the optimal sizing of the motor to rotate the waste collector. SOLIDWORK was used to perform the stress and deformation analysis towards the frame of the product. The results of the calculation were able to determine the optimal size of motor that could rotate and move trapped waste on the machine into the collector bin. Furthermore, the output of the analysis using SOLIDWORK also shows positive results where no failure indicator appears in the stress and deformation analysis. To conclude, this automatic drain rubbish collector was successfully designed, fabricated. and works perfectly. This product has been tested and it has removed most of the waste inside the drainage system